The Final Frontier: Confidentiality and Privacy in the Cloud - Rocha, Francisco (2012)
The boundary between the trusted inside and the untrusted outside blurs when a company adopts cloud computing. The organization's applications and data are no longer onsite, fundamentally changing the definition of a malicious insider.